EMI pioneers: Exploring Professors’ Experiences with English as a Medium of Instruction in a Brazilian university - Ribeiro, Juliana Michelon; Hendges, Graciela Rabuske; Rodrigues, Gabriel Salinet (Colombian Applied Linguistics Journal, 2024)
This study is part of a project aimed at mapping the implementation of English as a Medium of Instruction (EMI) at the Federal University of Santa Maria (UFSM). EMI is the use of English in teaching and learning content in curricular courses at universities where the language of instruction is not English (Dearden, 2014). The interest in EMI at the UFSM is linked to national and local internationalization policies. Despite the absence of a specific EMI policy at the UFSM, isolated EMI initiatives have been mapped (Rodrigues, 2019). This study examines perspectives of three professors regarding these initiatives to identify motivations, conditions, concerns, positive and negative outcomes, and needs. Data were collected from three sources: professors’ answers to an online questionnaire, interviews, and information retrieved from their curricula on the Lattes platform. Results indicate that the main characteristics of the EMI experiences are confidence in professors’ attitudes, support from the disciplinary community, and a pedagogical approach that emphasizes flexibility and diversity in students’ English use. These findings are expected to inform institutional actions related to EMI, such as policies and projects to support EMI professors and students.